Neutrophil-to-Lymphocyte Ratio as a Predictive Biomarker for Stroke Severity and Short-Term Prognosis in Acute Ischemic Stroke With Intracranial Atherosclerotic Stenosis - Ying, Yuanlin; Yu, Fang; Luo, Yunfang; Feng, Xianjing; Liao, Di; Wei, Minping; Li, Xi; Huang, Qin; Liu, Zeyu; Zhang, Lin; Zhao, Tingting; Tu, Ruxin; et al. (Frontiers in Neurology, 2021)
Background: Neutrophil-to-lymphocyte ratio (NLR) is an indicator of poor prognosis in acute ischemic stroke (AIS), but associations between NLR with stroke severity and prognosis of intracranial atherosclerotic stenosis (ICAS)-related ischemic events have not been well elucidated; therefore, we aimed to evaluate whether admission NLR levels correlate with the early stroke severity and short-term functional prognosis in patients with symptomatic ICAS (sICAS). Methods: This retrospective study enrolled 899 consecutive patients with AIS attributed to ICAS at Xiangya Hospital stroke center between May 2016 and September 2020. The initial stroke severity was rated by the admission National Institutes of Health Stroke Scale (NIHSS) scores, and the short-term prognosis was evaluated using the 14-day modified Rankin Scale (mRS) scores after stroke onset. A severe stroke was defined as NIHSS >8; an unfavorable functional outcome was defined as mRS scores of 3-6. Admission NLR was determined based on circulating neutrophil and lymphocyte counts. Results: The median admission NLR of all patients was 2.80 [interquartile range (IQR), 2.00-4.00]. In univariate analysis, admission NLR was significantly elevated in patients with severe stroke and poor short-term prognosis. After multivariate adjustment, admission NLR levels were significantly correlated with severe stroke [odds ratio (OR), 1.132; 95% confidence interval (95% CI), 1.038-1.234; P=0.005] and unfavorable short-term prognosis (OR, 1.102; 95% CI, 1.017-1.195; P=0.018) in Model 1. In Model 2, the highest NLR tertile (≥3.533) remained an independent predictor of severe stroke (OR, 2.736; 95% CI, 1.590-4.708; P<0.001) and unfavorable functional outcome (OR, 2.165; 95% CI, 1.416-3.311; P<0.001) compared with the lowest NLR tertile (<2.231). The receiver operating characteristic (ROC) curves showed the predictability of NLR regarding the stroke severity [area under the curve (AUC), 0.659; 95% CI, 0.615–0.703; P<0.001] and short-term prognosis (AUC, 0.613; 95% CI, 0.575–0.650; P<0.001). The nomograms were constructed to create the predictive models of the severity and short-term outcome of sICAS. Conclusions: Elevated admission NLR levels were independently associated with the initial stroke severity and could be an early predictor of severity and poor short-term prognosis in AIS patients with ICAS, which might help us identify a target group timely for preventive therapies.